1960´s in Britain and The Beatles - Milatová, Kateřina (Univerzita Pardubice, 2020)
The aim of the thesis is to clarify extensive social changes that happened in the sixties in Britain. The thesis will focus on working-class and youth. These changes were reflected in song production of the Beatles, the Rolling Stones and the Who. So that the analysis would be successful, it was necessary to point out the most important changes in the theoretical part, which contributed to inspiration of the lyrics and subsequently to analyse the differences between the bands.
60. léta v Británii a Beatles
Keywords: working class; changes; Beatles; the sixties; songs; youth; dělnická třída; změny; Beatles; 60. léta; písně; mládež